Multiple Surgeries Due To Pneumaturia, Cystolithiasis and Neurogenic Bladder in a Case with Munchausen Syndrome - Penbegul, Necmettin; Bozkurt, YASAR; Yildirim, Kadir; Sancaktutar, Ahmet Ali; Soylemez, Haluk; Atar, Murat; Bez, Yasin (Urology Journal, 2014)